Transcirculation Embolization to New Territory During Mechanical Thrombectomy for Acute Ischemic Stroke. (April 2022) - Burke, Devin J.; Aziz, Yasmin N.; Shah, Kavit; Jadhav, Ashutosh P.
Embolization in new territories (ENT) is a known complication of mechanical thrombectomy with incidence dependent upon a variety of procedural factors. We present 2 cases of anterior circulation to posterior circulation ENT. These cases were managed with manual aspiration thrombectomy with excellent radiographic and clinical outcome. We present the available literature involving ENT along with our experience in management.